Rotenone Induces a Neuropathological Phenotype in Cholinergic‑like Neurons Resembling Parkinson’s Disease Dementia (PDD) (2024)
ABSTRACT: Parkinson's disease with dementia (PDD) is a neurological disorder that clinically and neuropathologically overlaps with Parkinson's disease (PD) and Alzheimer's disease (AD). Although it is assumed that alpha-synuclein (α -Syn), amyloid beta (Aβ), and the protein Tau might synergistically induce cholinergic neuronal degeneration, presently the pathological mechanism of PDD remains unclear. Therefore, it is essential to delve into the cellular and molecular aspects of this neurological entity to identify potential targets for prevention and treatment strategies. Cholinergic-like neurons (ChLNs) were exposed to rotenone (ROT, 10 μM) for 24 h. ROT provokes loss of ΔΨm, generation of reactive oxygen species (ROS), phosphorylation of leucine-rich repeated kinase 2 (LRRK2 at Ser935) concomitantly with phosphorylation of α-synuclein (α-Syn, Ser129), induces accumulation of intracellular Aβ (iA β), oxidized DJ-1 (Cys106), as well as phosphorylation of TAU (Ser202/Thr205), increases the phosphorylation of c-JUN (Ser63/Ser73), and increases expression of proapoptotic proteins TP53, PUMA, and cleaved caspase 3 (CC3) in ChLNs. These neuropathological features resemble those reproduced in presenilin 1 (PSEN1) E280A ChLNs. Interestingly, anti-oxidant and anti-amyloid cannabidiol (CBD), JNK inhibitor SP600125 (SP), TP53 inhibitor pifithrin-α (PFT), and LRRK2 kinase inhibitor PF-06447475 (PF475) significantly diminish ROT-induced oxidative stress (OS), proteinaceous, and cell death markers in ChLNs compared to naïve ChLNs. In conclusion, ROT induces p-α-Syn, iA β, p-Tau, and cell death in ChLNs, recapitulating the neuropathology findings in PDD. Our report provides an excellent in vitro model to test for potential therapeutic strategies against PDD. Our data suggest that ROT induces a neuropathologic phenotype in ChLNs similar to that caused by the mutation PSEN1 E280A.